the Development of a Minimum Data Set (MDS) for dental implants registry - Roya Naemi; Leila Shahmoradi; Amirreza Rokn; Niusha Sohrabi; Hamid Reza Barikani (Tehran University of Medical Sciences, 2023)
Objectives: Registries are powerful tools for the collection and distribution of valid and reliable data. The initial step in health information management is to design a minimum data set that can improve the collection of high-quality data from the registry. The present pilot study aimed to determine the optimal minimum data set for dental implants to effectively utilize at Tehran University of Medical Sciences, Tehran, Iran. Materials and Methods: This descriptive cross-sectional study was conducted in 2019 at Tehran University of Medical Sciences. A minimum data set checklist was developed based on our previous systematic review. The content validity of the minimum data set was approved by the recruited experts and the final minimum data set was established using the Delphi technique. Results: The minimum data set for dental implants consists of two separate sections - administrative and clinical data. The administrative portion includes two main segments: patient demographic data and clinic data, consisting of 12 data elements. The clinical part includes five main segments (patient clinical data, implant data, implant complications, implant loss, and implant follow-up), and contains 96 data elements. Conclusion: This study suggests a minimum set of data for dental implants that can aid in efficient management of information, facilitate evidence-based decision-making, and enable high-quality clinical research, evaluation of treatment results, monitoring, and benchmarking of care.